A fiscalização como instrumento de mitigação dos impactos ambientais na extração de minério agregado à construção civil: estudo sobre a exploração do seixo no município de Ourém/Pa - CAVALCANTE, Wanderson Marques (Universidade Federal do Pará, 2023)
The aforementioned research starts from the academic reflection of a citizen and countryman who experienced and still experiences the challenges of the researched place, the municipality of Ourém/PA, located in the Microregion of Guamá, in the northeast of Pará, about 150 km from the capital Belém. We investigate the environmental, social and economic impacts in their multiple aspects, caused by the exploitation of aggregate ores for civil construction, also known as non-metallic ores, such as: sand, pebbles and gravel. The study area of the research analyzed the exploitation of the ore known as pebble, which is used in civil construction works, this ore explored in the city of Ourém/PA, which is one of the main municipalities for sand and pebble exploration in the State of Pará. It is noteworthy that the extraction of pebble ore, widely used in civil construction in the Guajará Integration Region (Belém, Ananindeua, Marituba, Benevides and Santa Bárbara do Pará) has not received the deserved attention of public, private and research entities. academic, even though it is considered one of the most important ores for the Brazilian mineral sector in the field of civil infrastructure, which, due to the large volume, has sensitive consequences for the local socio-environmental context. In this sense, we seek to investigate whether the licensing and supervision of the municipality for this type of ore is efficient, considering that the municipality is the public entity responsible for licensing and inspection. As a methodology, the deductive method was used, using a reasoning that starts from a singular or particular premise for more general reflections. In the research, the study of the bibliographical, legislative and jurisprudential correlated to the subject was used. We sought to understand the relationship between the municipal inspection activity and the environmental consequences experienced by the exploited surroundings. The conclusion is that the action of the municipal public power falls short of the need, and the environmental impacts are an externality that will be left to society to solve.